2015
DOI: 10.1118/1.4926090
|View full text |Cite
|
Sign up to set email alerts
|

WE‐G‐204‐06: Grid‐Line Artifact Minimization for High Resolution Detectors Using Iterative Residual Scatter Correction

Abstract: Purpose: Anti‐scatter grid‐line artifacts are more prominent for high‐resolution x‐ray detectors since the fraction of a pixel blocked by the grid septa is large. Direct logarithmic subtraction of the artifact pattern is limited by residual scattered radiation and we investigate an iterative method for scatter correction. Methods: A stationary Smit‐Rοntgen anti‐scatter grid was used with a high resolution Dexela 1207 CMOS X‐ray detector (75 µm pixel size) to image an artery block (Nuclear Associates, Model 76‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Compared with contemporary commercial grids with strip‐frequencies from 40 to 80 lines cm −1 , the N35r8h1.7 grid has a low strip frequency. When this grid would be used in stationary with digital image receptors, grid‐line‐removing techniques 3,5–9 might be an optional solution to remove interference of grid‐line artifacts on making diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with contemporary commercial grids with strip‐frequencies from 40 to 80 lines cm −1 , the N35r8h1.7 grid has a low strip frequency. When this grid would be used in stationary with digital image receptors, grid‐line‐removing techniques 3,5–9 might be an optional solution to remove interference of grid‐line artifacts on making diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, gridlines resulted from grids with high‐grid‐frequency, such as 70 lines cm −1 , are still significant and interfere with the visibility of low contrast details 4 . When stationary grids are used with digital image receptors, grid‐line artifacts may be removed by image processing techniques 3,5–9 …”
Section: Introductionmentioning
confidence: 99%
“…Then each part of the image is corrected individually by iteratively varying the scatter value in the respective section of the scatter profile, to minimize the standard deviation of the grayscale values in that part of the image. In the previous study, we showed that as the grid lines (structure pattern) are removed from the image, the standard deviation of pixel values in the image also goes down 8 . Once all the parts are corrected, they are combined back to form the corrected original image.…”
Section: Methodsmentioning
confidence: 96%
“…In previous studies, we reported the results involving a simulated artery block phantom with a uniform frontal head equivalent phantom used as the scattering source to investigate the effectiveness of the method to remove the anti-scatter grid-line artifacts when a grid is used with a Flat Panel Detector (FPD) and high resolution CMOS detector. 6, 7, 8 …”
Section: Methodsmentioning
confidence: 99%